The Spread of Rural Industry in Lower Canada, 1831-1851 - Courville, Serge; Robert, Jean-Claude; Séguin, Normand (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractAs a contribution to a larger project which seeks to explore the contours of the socio-economy of Lower Canada in the nineteenth century, this paper utilises the 1831 and 1851 census data to define the extent, nature, and distribution of an essential component in the rural economy — industry — in the St. Lawrence axis during the first half of the nineteenth century. The aggregate census data suggest that a degree of numerical stagnation, or even deindustrialisation, occurred between 1831 and 1851, localised in the Montréal district. An analysis of the individual census schedules for 1851 indicates that no such deindustrialisation actually took place. What is revealed is a picture of great complexity in terms of type and distribution of industries over time. The evolution of the emerging rural industrial landscape is linked to population growth, expanding land settlement, and urbanisation. What emerges is a picture of an integrated economy based on a relatively well-developed structural exchange system.